The impact of polystyrene nanoplastics on plants in the scenario of increasing temperatures The case of Azolla filiculoides Lam - Bottega, Stefania (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 The Authors. Published by Elsevier Masson SAS.. All rights reserved.